The splicing handbook techniques for modern and traditional ropes - Merry, Barbara; Darmin, John 1937- (International Marine/McGraw-Hill, 2000)
The only book devoted completely to slicing today's ropes, this fully illustrated, step-by-step guide has been expanded and enhanced in this new edition and now covers wire splices, and splices in Spectra and Kevlar ropes as well as Dacron braid and traditional three-strand. The Splicing Handbook includes every splice project a boater will ever need.